Optimasilasi Penghimpunan Zakat Pasca Pandemi Covid-19 Melalui Digital Marketing - Hidayat, Rahmad (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
Zakat collection is the main pillar of Islamic philanthropic institutions. During the pandemic, there has been an increase in the number of online transactions so it is important to know how to optimize zakat collection through digital marketing. The methodology used in this research is a literature study. The absence of regulations that force Muslims in Indonesia to give zakat requires Amil Zakat Institutions to move faster, more actively, and innovatively to maximize zakat collection, including by maximizing digital marketing. This research is general and does not specifically discuss the application of digital marketing that has been carried out by an amil zakat institution. Digital marketing strategies that can be used to maximize the collection of zakat funds are using organic (unpaid) and paid (paid) methods. Organic fundraising methods consist of search engine optimization (SEO), organic social media, e-mail marketing, promotion using WhatsApp. While the paid fundraising method uses google ads, social media ads, youtube ads